PENGARUH PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 7E TERHADAP KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK KELAS VIII SMP NEGERI 1 HARAU - Amna, Dwi Mardinata (Jurnal Edukasi dan Penelitian Matematika, 2023)
Problem-solving ability is one of the abilities that students need to have in learning mathematics. Based on the results of observations at SMPN 1 Harau, it can be seen that students' mathematical problem-solving abilities are still low. One of the learning models that can be used to improve mathematical problem-solving abilities is the 7E Learning Cycle model. The purpose of this study was to analyze and describe whether the mathematical problem-solving abilities of class VIII students at SMP Negeri 1 Harau became better after the Learning Cycle 7E model was applied. The type of research used is pre-experimental with the One Group Pretest-Postest Design. The population in this study were class VIII students at SMP Negeri 1 Harau in the 2022/2023 academic year. Samples were taken using the Simple Random Sampling technique, class VIII.5 as the sample class. The research instrument used was a test of mathematical problem-solving abilities in the form of essay questions. Based on the results of data analysis for hypothesis testing, it was found that at a significant level, α = 0.05 with the t-test P-value = 0.000 was obtained. Because the P-value is ˂ α, it can be concluded that  is rejected. So it was concluded that the mathematical problem-solving abilities of students who learned by applying the 7E Learning Cycle model were better than the mathematical problem-solving abilities of students whose learning did not use the 7E Learning Cycle model in class VIII SMP Negeri 1 Harau.Keywords — Solving Mathematical Problem, 7E Learning Cycle.